Pengelompokan Objek Daya Tarik Wisata (ODTW) di Kota Banda Aceh Berdasarkan Cluster Analysis - Putri Zahara; Myna Agustina Yusuf; Zainuddin Zainuddin (Jurnal RAUT, 2022)
Banda Aceh City is the Capital of Aceh Province as one of the main tourist destinations with a variety of available tourist objects, but the development of the tourism sector in Banda Aceh City is still uneven, while the potential is quite varied and has the opportunity to be developed. The tourism sector can be developed by identifying the existing potential through the formation of a cluster of tourist attractions (ODTW) which can be a reference in determining the direction of development strategies. The purpose of this research is to classify ODTW which is analyzed from the potential value based on cluster analysis, the results of which are expected to be a basic reference for formulating a strategy for developing tourism objects in Banda Aceh City. The data analysis technique used is descriptive quantitative through two stages, namely scoring analysis to measure the potential value of each ODTW and cluster analysis through SPSS software to classify ODTW based on similar characteristics from the previous assessment of tourism potential variables. The variables studied were tourist attraction attractiveness, accessibility, basic facilities and complementary facilities for tourism activities. Sampling in this study used a non-probability sampling technique with a saturated sampling method, namely the sampling method if the total population is less than 30. The results of this study are the identification of ODTW members in the three clusters formed, namely cluster 1 with high ODTW potential, there are 2 ODTW, cluster 2 there are 11 ODTW which are ODTW with medium potential, and cluster 3 with low potential there are 4 ODTW. As for the results of the study, it can be recommended that ODTW which has a main priority scale to be developed is ODTW which is in cluster 3 and the second priority scale to be developed is ODTW which is in cluster 2, so that ODTW can be prioritized for its development so that it can encourage tourism growth in the City. Banda Aceh. Suggestions for further research in order to formulate appropriate strategies for each ODTW prioritized for development.